Zero nominal interest rates, unemployment, excess reserves and deflation in a liquidity trap - Ryu-ichiro Murota; Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2009)
We present a dynamic and monetary model that consistently explains such various phenomena as unemployment, deflation, zero nominal interest rates and excess reserves held by commercial banks. These phenomena are commonly observed during the Great Depression in the United States, the recent long-run stagnation in Japan, and the worldwide financial crisis triggered by the US subprime loan problem of 2008. We show that an excessive liquidity preference leads to a liquidity trap and thereby generates the phenomena.
Keywords: E12; E31; E41; E51; 330; Liquidity Trap; Zero Nominal Interest Rate; Persistent Unemployment; Excess Reserve; Deflation